The revolution that wasn't how digital activism favors conservatives - Schradie, Jen (Harvard University Press, 2019)
The 2016 presidential election launched a public debate about the role the internet plays in civic and political life. To explain the surprise election of President Trump, a long list of culprits has been identified: Russian hacks, bots, fake news, greedy and careless social networks. While these may have played a role at the edges, something far more profound and enduring is shaping digital activism on the internet in a way that favors conservatives over progressives. The Revolution That Wasn't examines the dynamics that have given a decided edge to voices on the right. The setting is North Carolina, where from 2011-2014, the author followed the political battle over the question of whether public sector employees should have the right to unionize. She tracked 34 groups across the political spectrum to understand the role digital media played in their activism and observed a rising tide of conservative digital activism that took the state to the right, resulting in the election of the most right-wing state government in the country. Using a mix of data and first-hand reporting, Schradie explains how factors such as resources, organization, class, and ideology combine to amplify messages from the right and dampen those from the left.--